The effect of SCD and LEPR genetic polymorphisms on fat content and composition is maintained throughout fattening in Duroc pigs. (November 2016) - Henriquez-Rodriguez, E.; Bosch, L.; Tor, M.; Pena, R.N.; Estany, J.
Abstract: The effects of the stearoyl-CoA desaturase ( SCD ; AY487830 : g.2228T > C ) and leptin receptor ( LEPR ; NM _ 001024587 : g.1987C > T ) polymorphisms on fat content and fatty acid (FA) composition were investigated throughout fattening. Samples of Longissimus thoracis (LT) and subcutaneous fat (SF) from 214 Duroc barrows were collected from 160 days to slaughter age (220 days) using a longitudinal design. Results indicated that the positive effect of the T allele at the SCD gene on monounsaturated FA and of the T allele at the LEPR gene on saturated FA are maintained throughout the growing-finishing period, both in LT and SF. In LEPR, however, compositional changes, particularly in SF, are a result of increased fatness. There is very limited evidence of genotype by age interaction, and thus it is concluded that the combined selection for the SCD T and LEPR C alleles is a good strategy to increase the MUFA/SFA ratio regardless of the age at slaughter. Highlights: The effect of age on two SNPs affecting fat composition in Duroc pigs is examined. The SNP at the SCD gene increased monounsaturated fatty acid content. The SNP at the LEPR gene increased fatness and saturated fatty acid content. The effects of both SNPs are maintained throughout fattening.